Comparative Analysis of the Application of RCM (Reliability Centered Maintenance) and TPM (Total Productive Maintenance) Methods Through the Perspective of FMECA (Case Study: CN235-220 MPA TNI AL Aircraft) - Brian Fitri Wahyudi; Rony Prabowo (Al-Makki Publisher, 2026)
This study aimed to analyze the reliability of the ACM, identify the main failure modes, compare the application of Reliability-Centered Maintenance (RCM) and Total Productive Maintenance (TPM) methods, and develop a risk management model based on Failure Mode, Effects, and Criticality Analysis (FMECA). The study employed a descriptive quantitative approach using a case study of the ACM P/N 782630-5 installed on the CN235-220 Maritime Patrol Aircraft (MPA) operated by Air Squadron 800, Pusat Penerbangan TNI Angkatan Laut (Puspenerbal TNI AL). The data consisted of historical maintenance records from 2016–2025, which were analyzed using the parameters of Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), availability, Overall Equipment Effectiveness (OEE), and FMECA. The results showed 21 malfunction incidents with a total downtime of 283 hours, an MTBF value of 190.48 hours, an MTTR value of 13.48 hours, and a failure rate of 0.00525 failures per hour. The components with the highest criticality levels were the bearings, rotors, and turbine wheels. Reliability analysis indicated that the recommended preventive maintenance interval was every 68–70 operating hours. The TPM analysis produced an availability score of 92.93%, performance efficiency of 96.69%, quality rate of 97.52%, and OEE value of 87.63%, indicating that maintenance effectiveness was categorized as good. The recommended maintenance strategy combined Condition-Based Maintenance, Scheduled Maintenance, Autonomous Maintenance, and Focused Improvement, integrated with risk management to improve ACM reliability and enhance aircraft operational readiness.